2009
DOI: 10.4314/kjbm.v1i1.43817
|View full text |Cite
|
Sign up to set email alerts
|

The Egg or the Chick first; saving or GDP Growth: Case for Kenya

Abstract: This paper adopts the Hendry Model with a two-step method to model a saving function for Kenya. The Model uses a complex dynamic specification that includes lagged dependent and the independent variables. The paper finds that a 1% increase in GDP growth rate leads to a 0.5% increase in private saving in the long run which is consistent with the life cycle hypothesis. A striking result in the saving function is the positive effect that population growth rate seems to have on private savings which puts into ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…[31] Waithima (2008) used the Hendry Model with a two-step method to model a saving function for Kenya. He observed that a 1% increase in GDP growth rate causes a 0.5% increase in private saving.…”
Section: Household Saving Causes Economic Growthmentioning
confidence: 99%
“…[31] Waithima (2008) used the Hendry Model with a two-step method to model a saving function for Kenya. He observed that a 1% increase in GDP growth rate causes a 0.5% increase in private saving.…”
Section: Household Saving Causes Economic Growthmentioning
confidence: 99%
“…The sign of the coefficient of GDPG is positive which shows the long-run positive and insignificant relationship between GDPG and GDS. The studies by Waithima, 2008;Odhiambo, 2009;Oladipo, 2010 andMisztal, 2011 have found the positive impact of GDS on GDP growth.…”
Section: Long Run Resultsmentioning
confidence: 97%
“…Dan secara umum dapat dilihat bahwa GDP dan FDI yang tinggi, juga akan mendorong tingkat tabungan yang tinggi juga di Indonesia. Kesimpulan ini didukung juga oleh penelitian yang dilakukan oleh Abu (2010) di Nigeria, Waithima (2008) dan Olajide (2009).…”
Section: Hasil Dan Pembahasanunclassified
“…Hasil penelitian menunjukkan bahwa, Indonesia lebih condong sepakat dengan teori yang disampaikan oleh Keynes bahwa di Indonesia tingkat tabungan dipengaruhi oleh GDP dan FDI. Hasil yang ditemukan dalam penelitian ini sejalan dengan temuan peneliti lain diantaranya adalah Abu (2010) di Nigeria, Waithima (2008) dan Olajide (2009).…”
Section: Penutup 51 Kesimpulanunclassified